Saprophytic production of clavine alkaloids and activity of hydroxymethylglutaryl-CoA reductase - Kren, V; Pazoutová, S; Rylko, V; Rehácek, Z (Folia microbiologica, 1986)
In submerged Claviceps cultures the activity of hydroxymethylglutaryl-CoA reductase preceded the increase of alkaloid production and of sterol content. During the first alkaloid phase, cell mevalonate was involved in the biosynthesis of both alkaloids and steroids. In the second production phase, it was predominantly used for alkaloid synthesis. Hydroxymethylglutaryl-CoA reductase appears to be a suitable target for physiological manipulation to increase clavine alkaloid yields.
Keywords: ergoliny; námelové alkaloidy; Ergot Alkaloids; Claviceps; steroly; Sterols; Ergolines; Hydroxymethylglutaryl CoA Reductases; hydroxymethylglutaryl-CoA-reduktasy